Cutting Whole Length or Partial Length of Internal Anal Sphincter in Managementof Fissure in Ano (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
A chronic anal fissure is a common painful perianal condition.The main operative procedure to treat this painful condition is a lateral internal sphincteretomy (LIS).The aim of study is to compare the outcome and complications of closed LIS up to the dentate line (whole length of internal sphincter) or up to the fissure apex (partial length of internal sphincter) in the treatment of anal fissure.It is a prospective comparativestudy including 100 patients with chronic fissure in ano. All patients assigned to undergo closed LIS. Those patients were randomly divided into two groups: 50 patients underwent LIS to the level of dentate line (whole length) and other 50 patients underwent LIS to the level of fissure apex (partial length). Patients were followed up weekly in the 1st month, twice monthly in the second month then monthly   for next 2 months and finally after 1 year. There was satisfactory relief of pain in all patients in both groups & complete healing of the fissure occurred. Regarding post operative incontinence no major degree of incontinence occur in both group but minor degree of incontinence persists In 7 patients after whole length LIS after one year. In conclusion, both whole length & partial length LIS associated with improvement of pain, good chance of healing but whole length LIS associated with more chance of long term  flatus incontinence. Hence,we recommend partial length LIS as treatment forchronic anal fissure.